Length of stay in hospital and rehabilitation centers after stroke in Arab countries and Saudi Arabia: a systematic review and meta-analysis - Abdullah I. Alhusayni; Abdullah H. Alzahrani (Annals of Saudi Medicine, 2025)
BACKGROUND: Stroke rehabilitation is a vital component of post-stroke care, and the length of stay (LOS) in hospitals and rehabilitation centers varies across healthcare systems. This systematic review and meta-analysis assessed LOS among stroke survivors in Arab countries. METHODS: A comprehensive literature search identified studies reporting LOS in stroke rehabilitation. A comprehensive literature search from the inception until March 2025 identified studies reporting LOS in stroke rehabilitation. RESULTS: A total of 18 publications (25 datasets) involving 12 690 individuals were included in the meta-analysis. The pooled mean LOS was 25.67 days [95% confidence interval (CI): 16.22–35.11]. Subgroup analyses showed a longer LOS in Saudi Arabia (37.03 days, 95% CI: 24.11–49.95) compared to other Arab countries (8.87 days, 95% CI: 4.90–12.84), and in rehabilitation centers (46.71 days, 95% CI: 33.18–60.24) compared to acute hospital settings (9.07 days, 95% CI: 5.27–12.86). LOS varies widely across Arab countries and care settings. CONCLUSION: These findings highlight the need to examine whether differences in LOS are associated with functional recovery and healthcare efficiency. However, substantial heterogeneity across studies and a lack of outcome data limit the interpretability of the results.